Dinamica de 10,24 ha de um trecho de floresta estacional semidecidual, Galia, Alvilandia, SP, Brasil - Barreto, Tiago Egydio, 1979- (2009)
Orientadores: Ricardo Ribeiro Rodrigues, Maria Teresa Zugliani Toniato